Innovation in Teaching The General Course of Indonesian Language with a Project-Based Learning Approach at Hamzanwadi University - Eva Nurmayani; Lalu Mas'ud; Muh. Jaelani Al-Pansori; Herman Wijaya (PAEDAGOGIA, 2024)
The purpose of the study was to describe the application of the Project-based Learning (PjBL) model as the chosen alternative in relation to the maturation of learners who are oriented toward Indonesian language learning processes and products. The research method used is descriptive qualitative. The research subjects are first-year students of Hamzanwadi University in the academic year 2023/2024. The data sources are the results of performance observations and product portfolios. Data analysis was conducted qualitatively through tabulation and interpretation of General Work Criteria indicators. The results describe the PjBL model through its six steps, and the General Work Criteria (KKU) can help students achieve CPL, as evidenced by the KKU average score of 86. Through the PjBL model, students are able to publish ideas, ideas, knowledge, and research results, and have a working role equal, social sensitivity and concern; apply science and technology; have good morals, ethics, and language personality, and have a role as a proud citizen of the language with an anthology final average score of 86.2 as a final project. Based on these results, it can be concluded that the PjBL model can support the achievement of Indonesian language learning in producing written works and increasing collaboration, social work, and mastery of science and technology.